Sheep Bot Fly Oestrus ovis Linnaeus (1761) (Insecta: Diptera: Oestridae) - Hannah Sholar; Jennifer Lynn Gillett-Kaufman (EDIS, 2020)
The sheep bot fly, Oestrus ovis, is an obligate parasite found all over the world. It cannot complete its life cycle without parasitizing the nasal passages, frontal and maxillary cavities, and sinuses of sheep. Unlike other flies, females do not lay eggs, instead depositing droplets containing live larvae into the nostrils of sheep. This 4-page fact sheet written by Hannah A. Sholar and Jennifer L. Gillett-Kaufman and published by the UF/IFAS Entomology and Nematology Department describes the life cycle of the pest and its veterinary significance and management. https://edis.ifas.ufl.edu/in1267